Effect of low-dose, repeated exposure of contaminants of emerging concern on plant development and hormone homeostasis. (September 2019) - McGinnis, Michelle; Sun, Chengliang; Dudley, Stacia; Gan, Jay
Abstract: Treated wastewater is increasingly used to meet agriculture's water needs; however, treated wastewater contains numerous contaminants of emerging concern (CECs). With exposure and uptake of CECs, phytotoxicity and health of crop plants is of concern, but is poorly understood. This study evaluated the effect of low-dose, chronic exposure to a mixture of 10 CECs, including 4 antibiotics, 3 anti-inflammatory drugs, 1 antiepileptic, 1 beta-blocker, and 1 antimicrobial, on lettuce ( Lactuca sativa ) and cucumber ( Cucumis sativa L.) plants. The CEC mixture was added in nutrient media at 1 to 20X of their typical levels in treated wastewater effluents. Biological endpoints including germination, growth, phytohormone homeostasis, and CEC bioaccumulation were determined. Exposure to the CEC mixture did not affect the germination rate of lettuce seeds, but stimulated root elongation and increased the root-to-shoot biomass ratio during a 7 d cultivation. A dose-dependent decrease in biomass was observed in cucumber seedling after a 30 d exposure, with the highest rate CEC treatment resulting in decreases of 51.2 ± 20.9, 26.3 ± 34.1, and 33.2 ± 41.7% in the below-ground, above-ground, and total biomass, respectively. Levels of abscisic acid were significantly elevated (p < 0.05) in the leaves, but decreased (p < 0.05) in the roots. The dose-response of auxin was characterized by a hormesis effect. A significant 6-fold increase in the stem auxin level was observed at the 1X CEC rate, followed by a decrease to 2-fold the control at the 20X rate. Leaf auxin concentrations also significantly increased at the 1X CEC rate to 16-fold, followed by a decrease at the highest CEC rate. The results of this study suggeste that chronic exposure to low levels of CEC mixtures may compromise the fitness of plants, and the impairments are underlined by alterations in hormone balances. Graphical abstract: Image 1 Highlights: Exposure of lettuce seeds and cucumber seedlings to low level, CEC mixtures. Seed germination and root/shoot ratio assessed. Phytotoxicity to cucumber seedlings evaluated. Levels of important phytohormones determined to relate to observed toxicity. Disruptions to hormone balances underline chronic phytotoxicity by CECs.